Flash‐Assisted Processing of Highly Conductive Zinc Oxide Electrodes from Water. (5th November 2015) - Della Gaspera, Enrico; Kennedy, Danielle F.; van Embden, Joel; Chesman, Anthony S. R.; Gengenbach, Thomas R.; Weber, Karl; Jasieniak, Jacek J.
Abstract : Fabricating high‐quality transparent conductors using inexpensive and industrially viable techniques is a major challenge toward developing low cost optoelectronic devices such as solar cells, light emitting diodes, and touch panel displays. In this work, highly transparent and conductive ZnO thin films are prepared from a low‐temperature, aqueous deposition method through the careful control of the reaction chemistry. A robotic synthetic platform is used to explore the wide parameter space of a chemical bath system that uses only cheap and earth abundant chemicals for thin film deposition. As‐deposited films are found to be highly resistive, however, through exposure to several millisecond pulses of high‐intensity, broadband light, intrinsically doped ZnO films with sheet resistances as low as 40 Ω □ −1 can be readily prepared. Such values are comparable with state‐of‐the‐art‐doped transparent conducting oxides. The mild processing conditions (<150 °C) of the ZnO electrodes also enable their deposition on temperature sensitive substrates such as PET, paving the way for their use in various flexible optoelectronic devices. Proof‐of‐concept light emitting devices employing ZnO as a transparent electrode are presented. Abstract : Highly conductive, intrinsically doped ZnO electrodes are prepared using a low‐temperature aqueous deposition and a flash light postprocessing. The aqueous bath chemistry favors the formation of oxygen deficient ZnO films, which are then flashed with millisecond light pulses to achieve record conductivity and high transparency. Deposition on PET substrates and indium‐tin‐oxide‐free optoelectronic devices is demonstrated.